A SYNTACTICAL ANALYSIS OF SIMPLE SENTENCES IN KEMBHANG BABUR - Evha Nazalatus Sa'adiyah Sy; Devie Reztia A (Premise: Journal of English Education and Applied Linguistics, 2019)
Syntax is the study of the principles and processes by which sentence that it is constructed in particular language. Whereas that every language in the world certainly has different structure. This research aim to answer: (1) What are kinds of simple sentence found in Kembhang Babur books? (2) What are the differences between English and Madurese in simple sentences? This research is a descriptive qualitative research, descriptively describing the syntactic structures of simple sentences in Kembhang Babur book. The writer followed the rule of the qualitative which the data describe in words as the basis of interpreting data. Words are of utmost importance to qualitative researchers. There are three kinds of simple sentences found in Kembhang Babur book could be classified into: (a) Affirmative sentences, (b) Negative sentences (c) Interrogative sentences. The differences in English sentence is; if this affirmative sentence Aux there is after NP, but in the interrogative sentence Aux there is before NP and there is auxiliary “do/does” as interrogative verb. In Madurese sentence is marked by the addition of the word “apah” which is put before NP. “Apah” is as question word in Madurese, not as an auxiliary.